Production of high-maltose syrup from selected rice (Oryz sativa L.) Bran by Enzymatic method - Diopol, Garry A.; Elegado, Francisco B.; Castillo-Israel, Katherine Ann T.; Torio, Mary Ann O.; Uy, Lawrence Yves C. (2023)
Rice bran is an underutilized rice by-product. This study develops a methodology to enzymatically produce high-maltose syrup from rice bran of PSB Rc18. Rice bran liquefaction wan conducted sequentially by screening and optimization using response surface methodology (RSM) to determine the optimum condition for dextrose equivalents (DE). The DE upon liquefaction was affected by a-amylase concentration, rice bran concentration, , 0.12% of a a-amylase concentration, 80 ०C, and pH 5 for 60 min. These optimum conditions of DE acquired in liquefaction were carried over in the saccharification process for maltose conversion of rice bran using RSM. The maltose conversion was affected by DE, temperature, and pH. The saccharification process yielded the highest maltose conversation of 47.78% acquired in combination with 15.6% DF, 335 units of B-amylase, 50 ०C, and pH 5 for 24 hr.
Keywords: Rice; Oryza sativa L